(3GdGbJUGO GdGSdGej (B:s (3GdfXGe h GdfXQjI (B/s - (3CHh GdaJhM, fLGM YHO GdYdje YHO GdhgGHs ((3GQHO(B: s (3YGde GdcJH GdMOjK(B, s, 2011)
(3GdGbJUGO GdGSdGej h GdGbJUGO GdJbdjOj , Yde GdGbJUGO GdGSdGej h YdGbJg HYdej Gdabg h GUhd Gdabg , GdGbJUGO GdGSdGej (B: (3GdePgH h GdfXGe , GNJdGa eYGjjQ GdJbjje Hjf GdfXe GdGbJUGOjI , GdfXQjI GdGbJUGOjI GdGSdGejI (B: (3GdGbJUGO GdhMOj , YOGdI JhRjY GdONd h GdKhQI aj GdGbJUGO GdGSdGej , HMK aj Cge eSJJHYGJ GdJWHjb GdGdRGej ddRcGI Ydi GdcaGAI , GdGbJUGO GdJLejYj (B: (3JMdjd GdONd Gdbhej , ebOQI GdGbJUGO GdGSdGej Ydi JMbjb caGAI GdJNUjU , GdfbhO h GdeUGQa GdGSdGejI , GWGQ ebJQM ddJfejI aj GdGbJUGO GdGSdGej , HYV GdeaGgje GdgGeI aj GdGbJUGO GdGSdGejs
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdGSdGejs; (3GdEbJUGO(B- (3Gdabg GdGSdGejs